Effects of chitosan and TiO2 nanoparticles on the antibacterial property and ability to self-healing of cracks and retrieve mechanical characteristics of dental composites - Reza Ravandi; Saeed Zeinali Heris; Salar Hemmati; Marziyeh Aghazadeh; Soodabeh Davaran; Nima Abdyazdani (Heliyon, 2024)
The aim of this study was to improve the self-healing properties of dental nanocomposite using nanoparticles of TiO2 and chitosan. We evaluated flexural and compressive strength, crack-healing, and self-healing lifespan after 3 months of water aging. The effect of the developed composite on cell viability and toxicity was assessed by an MTT assay on human alveolar basal epithelial cells (A549 cell line). The nanocomposite included 7.5 wt% polyurea-formaldehyde (PUF) and 0, 0.5, and 1 wt% n-TiO2 and chitosan. After the fracture, the samples were put in a mold for 1–90 days to enable healing. Then, the fracture toughness of the healed nanocomposites and the healing yield were measured. The flexural strength of the nanocomposite improved by adding 0.5 wt% n-TiO2, while the compressive strength increased after adding 0.5 wt% chitosan (p > 0.1). When these two materials were used simultaneously, the flexural strength was improved by around 2%; however, the compressive strength was unaffected. Compared to the other sample, the nanocomposite with 0.5 wt% n-TiO2 and chitosan had higher KIC-healing and self-healing efficiency. Self-healing efficacy had no significant effect of water aging over 90 days compared to one day (p > 0.1), demonstrating that the PUF nanocapsules were not damaged.